Exploring the Philosophical Concept of Emerson’s “The Over Soul” in His Essays - Minderop, Albertin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
The objective of this research is to demonstrate the deepest meaning of the philosophical concept of "The Over-Soul" by Ralph Waldo Emerson (1803–1882) found in some of his essays, which were considered to be too difficult to decipher as there are many symbols and metaphors. This paper discusses Bhagavad Gita and Sufism teaching as those religious epics influence Emerson’s work. In addition, the hermeneutical method of Paul Ricoeur as one philosophical approach is used to interpret symbols and metaphors in his essays. The result of the study concludes that “The Over Soul” or the “divine light” is able to provide the feeling of “Perfect Happiness” and become “the Whole-Man” by performing the following: having retrospect, doing introspection, contemplation, and meditation in order to reinforce self-control attitude.